Dimeric DNA Aptamer Complexes for High-capacity-targeted Drug Delivery Using pH-sensitive Covalent Linkages - Olcay Boyacioglu; Christopher H Stuart; George Kulik; William H Gmeiner (Elsevier, 2013)
Treatment with doxorubicin (Dox) results in serious systemic toxicities that limit effectiveness for cancer treatment and cause long-term health issues for cancer patients. We identified a new DNA aptamer to prostate-specific membrane antigen (PSMA) using fixed sequences to promote Dox binding and developed dimeric aptamer complexes (DACs) for specific delivery of Dox to PSMA+ cancer cells. DACs are stable under physiological conditions and are internalized specifically into PSMA+ C4-2 cells with minimal uptake into PSMA-null PC3 cells. Cellular internalization of DAC was demonstrated by confocal microscopy and flow cytometry. Covalent modification of DAC with Dox (DAC-D) resulted in a complex with stoichiometry ~4:1. Dox was covalently bound in DAC-D using a reversible linker that promotes covalent attachment of Dox to genomic DNA following cell internalization. Dox was released from the DAC-D under physiological conditions with a half-life of 8 hours, sufficient for in vivo targeting. DAC-D was used to selectively deliver Dox to C4-2 cells with endosomal release and nuclear localization of Dox. DAC-D was selectively cytotoxic to C4-2 cells with similar cytotoxicity as the molar equivalent of free-Dox. In contrast, DAC-D displayed minimal cytotoxicity to PC3 cells, demonstrating the complex displays a high degree of selectivity for PSMA+ cells. DAC-D displays specificity and stability features that may be useful for improved delivery of Dox selectively to malignant tissue in vivo.